First record of Didicrum Enderlein (Diptera: Psychodidae, Psychodinae) from the Northern Andes bioregion, with the description of a new species - Moya-Arévalo, Rosa Helena; Ibáñez-Bernal, Sergio; Suárez-Landa, María Teresa (Zootaxa, 2012)
Didicrum colombensis sp. nov. is described and illustrated based on male and female morphological characters. The discovery of this species in Colombia represents a significant range extension for Didicrum as all previously described species of this genus are distributed in the Australasian region and the southernmost portion of South America. A checklist of the World species of Didicrum is presented.